Information technology. Open systems interconnection. Structure of management information. Information technology. Open systems Interconnection. Structure of management information:Requirements and guidelines for implementation conformance statement proformas associated with OSI management Part 6, (15th May 1995) - British Standards Institution,
No abstract available